New Year’s Eve as a Case Study in Experimental Metaphysics: Exploring Global Consciousness in Random Physical Systems - Radin, Dean (Journal of Scientific Exploration, 2025)
This study explored the hypothesis that during moments of collective human focus and emotional resonance unexpected coherence will emerge in random physical systems. This mind-matter interaction hypothesis was tested during New Years Eve celebrations in each time zone using data from the Global Consciousness Project, a worldwide network of electronic truly random number generators. Analyses of data spanning the years 1998 to 2025 —including simple measures like mean shifts as well as changes in entropy, chaotic attractors, fractal dimensions, and Principal Components Analysis (PCA) —revealed statistically significant deviations at or within minutes of the stroke of midnight on New Years Eve, as compared to the same analysis applied to midnight transitions every other day of the year and to randomized permutation techniques (e.g., p = 4.8 × 10−7 for the PCA analysis). The study also found that the statistical deviations were stronger in time zones with higher vs. lower populations, suggesting that the magnitude of this psychophysical interaction was related to the number of minds engaged in a coherent focus of attention. Alternative mundane explanations, including possible environmental artifacts, were considered but deemed unlikely because the RNGs were specifically designed to exclude such influences. An imaginative roundtable discussion among the founders of quantum mechanics is used as a vehicle to discuss these results.